The combination effect of meropenem/sulbactam/polymyxin-B on the pharmacodynamic parameters for mutant selection windows against carbapenem-resistant Acinetobacter baumannii - Zhang, Jiayuan; Diao, Shuo; Liu, Yanfei; Wang, Hongxiang; Liu, Yuwei; Zhu, Shixing; Feng, Kun; Tang, Xiaoqian; Oo, Charles; Zhu, Peijuan; Lv, Zhihua; Yu, Mingming; et al. (Frontiers in Microbiology, 2022)
The objective of this study was to evaluate whether combinations of sulbactam, meropenem, and polymyxin-B could reduce or close the gap of mutant selection window (MSW) of individual antibiotics against Acinetobacter baumannii harboring OXA-23. MICs of three antimicrobials used alone and in combination (meropenem/polymyxin-B or meropenem/polymyxin-B/sulbactam) were obtained in 11 clinical isolates and mutant prevention concentrations were determined in 4 of the 11 isolates. All isolates were resistant to meropenem or polymyxin-B. Combining meropenem and polymyxin-B with or without sulbactam resulted in synergistic bactericidal activities. Pharmacokinetic (PK) simulations of drug concentrations in the blood and epithelial lining fluid coupled with pharmacodynamic (PD) evaluations revealed that the fractions of time over the 24-h in terms of free drug concentration within the MSW (fTMSW) and above the MPC (fT>MPC) were optimized by combination therapy. The resultant clinical regimens of meropenem, polymyxin-B, and sulbactam evaluated in the PK-PD analysis were 2 g q8h, 2.5 mg/kg loading dose followed by 1.5 mg/kg q12h, and 3 g q8h, respectively, in patients with normal renal function. Subsequent corresponding equivalent exposure regimens would depend on the extent of renal failure. The overall results indicate that combination antibiotics consisting of sulbactam/meropenem/polymyxin-B can confer potential efficacy against A. baumannii harboring OXA-23, and reduce the opportunity for bacteria to develop further resistance. This study provides a framework for pharmacodynamic evaluation of drug-resistant mutant suppression in an antimicrobial co-administration setting. The results thereby lay the groundwork for additional studies and future clinical confirmation is warranted.